On corporate risk management practices in Romanian companies - Horobet, Alexandra; Dumitrescu , Sorin; Joldes, Cosmin (Applied Studies in Agribusiness and Commerce, 2009)
The purpose of this paper is to provide an understanding of corporate risk management practices in Romanian companies, by investigating the risk management approaches Romanian companies take. Our main findings are that Romanian managers are not aware of the magnitude of exposure their companies have to various types of risk – hazard, operational, financial and strategic risks, while they are able to manage rather well all these risks, even the ones that have the lowest impact on the business. At the same time, risk management systems employed by Romanian companies are rather inarticulate and based on traditional approaches towards risk management, which might represent by itself a major source of risk, given the complexity of the business environment they face.